The Randomized Response Technique Application in the Survey of Homosexual Commercial Sex among Men in Beijing. - Xiangyu Chen; Qiaoqiao DU; Zongda Jin; Tian Xu; Jiachen Shi; Ge Gao (Iranian Journal of Public Health, 2014)
Traditional survey methods may cause refusals to respond or untruthful replies when encounter the sensitive questions. The Randomized Response Technique (RRT) is designed to decrease social desirability bias and obtain reliable estimates. This study aimed to apply these new methods on the sensitive questions survey.Simmons model was applied in the survey of issues relevant to commercial sex among men who have sex with men (MSM) in Beijing, China. Stratified two-stage sampling and stratified random sampling were applied.During July to December 2010 in Beijing, the commercial sex proportion among MSM was 0.051(95% CI: 0.017, 0.085), its estimated variance was 3.01×10(-4). The last male condom use rate during commercial sex was 0.778(95% CI: 0.746, 0.810), its estimated variance was 2.6×10(-4).We have introduced new approaches for the sensitive question survey among MSM. The new approaches are proved to be reliable and valid.